2022
DOI: 10.1177/07419325221105520
|View full text |Cite
|
Sign up to set email alerts
|

Rational Number Interventions for Students With Mathematics Difficulties: A Meta-Analysis

Abstract: Understanding rational numbers is critical for secondary mathematics achievement. However, students with mathematics difficulties (MD) struggle with rational number topics, including fractions, decimals, and percentages. The purpose of this systematic review was to describe the instructional foci of rational number interventions, determine the overall effect size, and explore potential moderators. Forty-three studies were included and 150 effect sizes were meta-analyzed using robust variance estimation. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Take, for example, fractions and decimals. As students progress through school, the need to use precision and incorporate fractions and decimals in their measurements becomes more necessary (Rojo et al, 2022). However, these skills may be challenging for students with LD in mathematics because they tend to require more time and need more scaffolded practice opportunities than their typically achieving peers in understanding rational numbers (Mazzocco et al, 2013).…”
Section: Research-article2023mentioning
confidence: 99%
See 1 more Smart Citation
“…Take, for example, fractions and decimals. As students progress through school, the need to use precision and incorporate fractions and decimals in their measurements becomes more necessary (Rojo et al, 2022). However, these skills may be challenging for students with LD in mathematics because they tend to require more time and need more scaffolded practice opportunities than their typically achieving peers in understanding rational numbers (Mazzocco et al, 2013).…”
Section: Research-article2023mentioning
confidence: 99%
“…One plausible way teachers can support students with LD is to incorporate number lines into their mathematics instruction. Number lines can help provide an underlying structure for representing the magnitude of rational numbers (Rojo et al, 2022), which can increase students’ precision in measurements (Dyson et al, 2020).…”
mentioning
confidence: 99%
“…However, for these interventions to be regarded as evidence-based instead of promising for students with learning disabilities, more research is needed. In addition, Rojo et al (2023) conducted a meta-analysis of the rational number intervention research and found few studies that included decimals and percentages. They emphasized the importance of understanding rational number notation using decimals in upper elementary grades and a need for additional research (Rojo et al, 2023).…”
Section: Rationale For Current Studymentioning
confidence: 99%
“…The acquisition of rational number understanding begins as early as second grade when students are introduced to fractions, and it builds throughout upper elementary and middle school, increasing in level of difficulty as students are required to engage in more complex applications of rational number knowledge (Rojo et al, 2022). Yet, one of the largest hurdles to rational number learning is that students struggle to adequately transition from whole number reasoning to rational number reasoning (Jordan et al, 2013; Van Hoof et al, 2017).…”
mentioning
confidence: 99%
“…This phenomenon, referred to as the whole number bias , may have significant implications for the acquisition of mathematical skills, particularly among students with learning disabilities (LD) in mathematics (Ni & Zhou, 2005). Students may struggle with the following topics due to the whole number bias (see Table 1): (a) magnitude (e.g., students may only consider the numerator or denominator within a fraction); (b) arithmetic (e.g., students may view each operand in a fraction arithmetic problem as two separate whole numbers, resulting in misapplication of operations to the two numerators and also the two denominators); (c) density (e.g., students may fail to understand that an infinite number of numbers exist between any two decimals or two fractions); and (d) translation (e.g., students may not understand fractions and decimals as alternative notations; Rojo et al, 2022; Tian & Siegler, 2018).…”
mentioning
confidence: 99%